Creating and negotiating collaborative spaces for socially just anti-bullying interventions for K-12 schools - Osanloo, Azadeh F.; Reed, Cynthia J.; Schwartz, Jonathan P. (Emerald Publishing Limited : Information Age Publishing, Inc., 2017)
Across the United States, schools face the daunting issue of confronting the widespread effects of bullying, which threaten the physical, emotional, and intellectual well-being and development of youth. Creating and Negotiating Collaborative Spaces for Socially-Just Anti-Bullying Interventions for K-12 Schools is a theoretically and empirically grounded edited volume that describes practical ways to address bullying at both systemic and individual levels. Central to the scope of the book is a diversity-focused approach to assessing and conceptualizing discrimination and bullying among marginalized youth, such as LGBTQ, mixed race, gifted and talented, and special needs populations.Interspersed with concrete, real-life examples, each chapter in the volume expands on the multiple dimensions of bullying as well as research-backed anti-bullying interventions. The book advances previous literature by addressing contemporary issues in bullying. Special topics include teacher-to-student bullying, cyberbullying, restorative justice practices, and assessment of attitudes toward addressing bullying.
Keywords: Bullying in schools -- United States -- Prevention.; Education -- Administration -- General.; Pre-school and kindergarten.; Educational administration and organization.; elektronické knihy; electronic books